The adoption of big data analytics in South African financial institutions - Dlamini, Mzwandile (University of the Witwatersrand, Johannesburg, 2024)
Financial institutions by nature of their operations handle a lot of information, to examine and extract value from the data they receive. However, with the increasing automation, the data they receive have change in volume and the speed at which it is generated necessitating them to learn new techniques to analyse this voluminous data also known as Big Data (BD). Much as this is so, there are still fewer frameworks and models that have been developed to guide the adoption of this big data analytics (BDA). More still, the available frameworks are not contextualised to perspectives of South African financial institutions. The main goal of the study was to develop a framework for the adoption of BDA in South African financial institutions. The technology-organisation-environment (TOE) framework was used as the underpinning theory for this study based on which a conceptual framework was designed. A close-ended questionnaire was used to collect data from a South African financial institution in the Gauteng Province. Random sampling to select the 130 respondents that participated in the study. Results revealed that technological factors, technological characteristics, users’ perception towards technology, organisational factors due to top management support, individual characteristics and BD characteristics are essential in BDA adoption. However, the results also indicated that organisational factors, organisational factors due to size and structure of the organisation and environmental factors were not significant in the adoption of BDA. This study contributes to the studies of BDA adoption in organisations in developing nations. The degree of influence that different factors have on adoption of technologies differs depending on the context, future studies can leverage these findings to extend research in BDA adoption. This study recommends that future research expand data collection to include more organisations that are categorised as financial institutions to properly generalise the study’s findings.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Big data analytics; Technologoy adoption; Financial institutions; SDG-8: Decent work and economic growth